The Role of Avoidance Procrastination Towards Academic Achievement of University Student - Widia Sesha Riani; Era Lovi Setyowati; Dyah Lusiana Prabandari (Jurnal Syntax Admiration, 2024)
Aim of this study is to identify the role of avoidance procrastination towards academic achievement of university student. This research is quantitative research by using correlation methods involving 400 undergraduate male and female university students’ classes of 2014 until 2017 in Indonesia. Two Instruments used for this research are: variable of avoidance procrastination is measured by using McCown & Johnson’s (1989) Adult Inventory of Procrastination (AIP) scale, and academic achievement variable is measured by using the Grade-point Average (GPA). We use Simple Linear Regression Analysis as our data analysis methods by using IBM SPSS Ver.22 software. Results of our study is that avoidance procrastination produces negative influence towards academic achievement, such that university students who has higher avoidance procrastination have lower rates of academic achievement, while university students who has lower avoidance procrastination achieve higher rates of academic achievement. This study is proven by regression coefficient value of –0,81 and significancy value 0,000 < 0,05 (p – value < 0,05).